Synthesis, Characterization and Photocatalytic Activity of CoFe2O4/Fe2O3 Dispersed in Mesoporous KIT-6 - Johnatan de Oliveira Soares; Wesley Eulálio Cabral Cavalcanti; Marco Antonio Morales Torres; Sibele Berenice Castella Pergher; Fernando José Volpi Eusébio De Oliveira; Tiago Pinheiro Braga (Nanomaterials, 2022)
The present work aimed to synthesize and characterize a solid based on CoFe2O4/Fe2O3-KIT-6 and evaluate its performance in the photocatalytic degradation of the remazol red ultra RGB dye. By analyzing XRD, N2 physisorption, and Mössbauer results, it was possible to identify that the desired CoFe2O4/Fe2O3 phase was achieved, which maintained its structural properties. The FTIR-pyridine indicated the presence of Lewis acid sites, while TPD-CO2 showed a large amount of weak basic sites. The band-gap energy indicated that the compound can be applied in photocatalytic degradation under UV/visible light, with the possibility of magnetic separation at the end of the reaction. The photocatalysis results indicated that there was complete degradation of the remazol red ultra RGB dye within 1 h of reaction. Despite the absence of H2O2, the combination of the proposed photocatalyst with the anatase phase (TiO2) showed significant improvements in the degradation process. The proposed mechanism for complete dye degradation indicated that a sequence of radical reactions is necessary, generating oxidant species such as •OH and the final products were CO2 and H2O.